Paradox of Low CA-125 in Patients with Decompensated Congestive Heart Failure - Raquel López-Vilella; Borja Guerrero Cervera; Víctor Donoso Trenado; Julia Martínez-Solé; Sara Huélamo Montoro; Valero Soriano Alfonso; Franco Appiani; Luis Martínez Dolz; Luis Almenar-Bonet (Biomedicines)
Background/Objectives: Patients diagnosed with decompensated congestive heart failure (HF) often have elevated CA-125 levels, attributed to systemic congestion. However, a subgroup of patients presents with normal CA-125 levels. The primary objective of this study was to characterize the clinical, analytical, and echocardiographic profiles of patients admitted for decompensated congestive HF according to their CA-125 levels. The secondary objective was to analyze mortality after discharge. Methods: We conducted a retrospective study of patients hospitalized for a decompensated congestive HF episode. Recruitment was consecutive over more than 4 years (December 2019–June 2024), with 3151 patients recruited. Scheduled admissions, transfers from other hospitals, pulmonary congestion patterns, mixed patterns, and low output were the exclusion criteria. The final number of patients included was 166, all with an isolated systemic congestion pattern: CA-125 ≤ 50 U/mL: 38, and CA-125 > 50 U/mL: 128. Results: The comparative analysis between the groups showed that patients with CA-125 ≤ 50 U/mL were more often women (p < 0.05). They also had lower bilirubin and GOT/AST levels (p < 0.05). The percentage of patients with a preserved left ventricular ejection fraction (≥50%) was higher in the CA-125 ≤ 50 U/mL group (p < 0.05). The right ventricular (RV) size and inferior vena cava (IVC) were enlarged in both groups but with no significant differences (p < 0.05). However, the degree of RV dysfunction was greater in the CA-125 > 50 U/mL group, while the proportion of patients with inspiratory collapse of the IVC was higher in the CA-125 ≤ 50 U/mL group (p < 0.05). Survival curves differed from the first month and throughout the follow-up, with higher mortality in the CA-125 > 50 U/mL group. Thus, the probability of being alive at the end of the follow-up was over 50% in the CA-125 ≤ 50 U/mL group, while in the CA-125 > 50 U/mL group, it was around 25% (p < 0.05). Conclusions: The proportion of patients with decompensated congestive HF and systemic congestion who present with a low CA-125 level is close to 25%. These patients are mostly women with a preserved ejection fraction and inspiratory collapse of the IVC of >50%. Moreover, they have a higher survival rate, so a low CA-125 could help identify a subgroup of patients with a better prognosis.